PROTOTYPE ROBOT UNTUK MENENTUKAN ARAH KIBLAT DENGAN TANDA SHAF SHOLAT - Hakim, Luqman; Raharjo, Rifqi Budi; Waluyo, Didik Dwi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Qibla is the center for Muslims in doing daily prayers. There have been many studies on determining the Qibla direction that utilizes spherical trigonometry method to generate the Qibla direction from position latitude and longitude. However, no previous studies that determine the direction of the Qiblah while making rows line prayer. Therefore at the end of the project, the Qibla direction indicator system in the form of a prototype robot that could determine the direction of the Qiblah while making rows line prayer. GPS data in the form of latitude and longitude is calculated automatically by the microcontroller to obtain the direction of Qibla. The data is then compared with the data of digital compass. Robot will spin up the difference in digital compass data is not greater than 5 Â° with the calculation of Qibla. If the Qibla direction are correct, then the robot will rotate to the left 90 Â° from the direction of the Qiblah and the robot will make a straight line extending rows of lines as a sign of prayer. When the proximity sensor detects an obstacle in front, the robot will stop making a line. From the experimental results, the robot can create the rows with an average error of 0.0083325%.